2018
DOI: 10.1111/jocn.14692
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ attitudes, beliefs and practices on sexuality for cardiovascular care: A cross‐sectional study

Abstract: Aims and objectives To describe nurses’ attitudes, beliefs, and practices regarding sexuality care for patients with cardiovascular disease. Background Limited sexual activity is common among patients with cardiovascular disease, yet assessment of sexuality and counselling is frequently not undertaken by nurses. Design Cross‐sectional study. Methods This study recruited 268 cardiac nurses from seven tertiary hospitals in five cities of Henan province. The Sexual Attitudes and Beliefs Survey, along with investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
2
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 36 publications
1
16
2
10
Order By: Relevance
“…The results of the present study were found to be similar to the study that was conducted by Saunamäki et al (2010) in Sweden(5). Also, it was found that the results of the present study were lower than the results of the studies that were conducted in countries where eastern culture is dominant, such as China and Jordan (1,2,11). The results were found to be higher Fearing that patients might be offended/embarrass 88 74.6 than the results of the studies that were conducted in countries where western culture is dominant, such as America and Portugal (13,19).…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…The results of the present study were found to be similar to the study that was conducted by Saunamäki et al (2010) in Sweden(5). Also, it was found that the results of the present study were lower than the results of the studies that were conducted in countries where eastern culture is dominant, such as China and Jordan (1,2,11). The results were found to be higher Fearing that patients might be offended/embarrass 88 74.6 than the results of the studies that were conducted in countries where western culture is dominant, such as America and Portugal (13,19).…”
Section: Discussioncontrasting
confidence: 66%
“…Studies on sexuality show that patients are willing to tell their sexual problems to nurses; however, nurses cannot be efficient in sexual care both because their knowledge about sexuality is not adequate and their beliefs about sexual care. (10)(11)(12)(13)(14)beliefs, and practices regarding sexuality care for patients with cardiovascular disease. Background: Limited sexual activity is common among patients with cardiovascular disease, yet assessment of sexuality kıma ilişkin danışmanlık verirken kendilerini rahat hissetme puan ortalamalarının ise 10 üzerinden 4,32±2,63 (min:0 maks:10) olduğu saptanmıştır.…”
Section: Introductionmentioning
confidence: 99%
“… 29 , 30 , 34 Neither did shy men perceive HPs’ address of sexuality as annoying, bothersome or offensive, which is an important new finding because the fear of offending their patients is a well-known barrier for HPs in addressing sexuality. 14 , 15 , 60 Attending group sessions where HPs address sexuality could be a potentially emotional effort for some of the men; however, even the shyer men accepted the address of sexuality in group sessions by choosing to keep their head down. Thus, the shy men would never themselves initiate a conversation about sexuality and therefore it is of great importance that the HPs initiate communication on sexuality and ED, and how they address the topic, listen to and work with patients to create a comprehensive management plan regarding sexual problems.…”
Section: Discussionmentioning
confidence: 99%
“…13 Common barriers for HPs' address of sexuality and sexual issues such as ED are due to lack of HP education, competences and professionalism in the field of sexuality, or HPs' perception that addressing sexuality is embarrassing for patients, being too intimate, private and potentially offensive to discuss. [14][15][16][17][18] Furthermore, HPs' reason for not inquiring about sexual function and ED can be attributed to their impression of cardiac patients' lack of readiness and reluctance to bring up the subject. 14,18,19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation